A Multimode Network Steganography for Covert Wireless Communication Based on BitTorrent. (5th July 2020) - Wang, Mingqian; Gu, Weijie; Ma, Changshen
Abstract : Network steganography is a hidden communication technique, which utilizes the legitimate traffic as the vehicle to transfer the secret information covertly over the untrusted network. BitTorrent (BT) is one of the most prevalent P2P services for transmitting video files over wireless networks. An enormous amount of video data is transmitted over BitTorrent traffic continuously, to make it potentially available for confidential information transfer. Hence, in this paper, the BitTorrent file-sharing service of P2P is chosen as the host for information hiding, and a multimode steganographic method based on Bitfield message is proposed. Taking advantage of BitTorrent cooperative transmission and the non-content-authentication mechanism of Bitfield message, the secret information is delivered during the exchange process of BitMapInfo between two peers. The steganographic mode is dynamically selected in view of the secret size, achieving adaptive bandwidth. The experimental results show that our scheme can resist statistical-based detection effectively and outperform the existing method by obtaining a lower degree of detection rate under machine learning-based steganalysis.